Psychometric properties of the Albanian version of the effort-reward imbalance model in a sample of healthcare workers in Shkodra, Albania hospital - Pjetri , Emiljano; Shabani , Zamira; Shala, Irena; Bekteshi, Adem (Medicni Perspektivi, 2025)
The goal of this study was to test the reliability and validity of the Albanian version of the 23-item effort-rewardimbalance (ERI) questionnaire and to analyze its association with job dissatisfaction in a sample of Albanian healthcare professionals working in Regional Hospital in Shkodra.A cross-sectional study on a representative sample was carried out. Descriptive statistics was performed. Cronbach’s alpha coefficient was calculated to estimate the internal consistency reliability. Significant differences were calculated using ANOVA. A total of 270 study participants were involved in the study, and the response rate was 81% (219/270). Women and those with master degree predominated. The consistencies of the three scales: effort, reward, and overcommitment were obtained. Mean ratio effort-reward was all the time higher than 1 for all cases in the study. Results show a significant difference for effort and overcommitment based on gender and department in which a person is working.This study is the first one supporting psychometric properties of the Albanian version of the ERI model. Based on the results of this study the Albanian version of the ERI questionnaire is considered a reliable and valid instrument for measuring psychosocial stress at work. Our suggestion is that it is applicable to Albanians working in healthcare sector